ESPAÇOS PRATICADOS, CONSUMO E CONSTITUIÇÃO DE SUJEITOS NA DISCOGRAFIA DE TONICO E TINOCO (1940-1981) - Renzcherchen, Anderson Teixeira (2018)
The central proposal of this dissertation is to promote a densification in the analysis of the songs for a proposition of the constitution of the subject caboclo and sertão, as well as your culture, through composers and their letters.In this dissertation the temporal boundaries took place based on the first song sung in Tonico and Tinoco career in a radio program the Jorginho do Sertão that was at the beginning of the Decade of 1940 and the last recorded music that had the word sertão in your title, Museu do sertão of 1981. This portrait of the cultural hinterland can be interpreted as the imaginary of the caboclo, considering the origin of country duo. In addition to this premise, will be proposed a mapping in the terminological designations that are the word "caboclo", both in academic studies, as in. The theoretical basis is guided in Certeau, Foucault and Freud. In them it is possible to express the daily life within the experiences of the rural man, especially the caboclo. Within this dissertation also fits stress the importance of the music industry, radio and television for the space of country music could happen and provide a rooting of the caboclo who sought better living conditions during the exodus in rural Brazil. The music served in this sense as a hold the ills that urban culture imposed upon rural man will try a new means of survival. In short, the analysis of the songs, a search of your projection on the market and the main points that involve the letter as the word sertão, the denomination owns of the caboclo, the patriotic pride of this subject and the importance that nature has in the life of the caboclo, in your existence as a rural man and especially regarding the term caboclo, being the nature key so that it can be granted within the regionality of your space practiced.